Inhibitory effects of Clostridium butyricum culture and supernatant on inflammatory colorectal cancer in mice - Pu, Wenfeng; Zhang, Hong; Zhang, Tao; Guo, Xiaoguang; Wang, Xiaoqing; Tang, Shaohui (Frontiers in Immunology, 2023)
Clostridium butyricum (CB) is a spore-forming, gram-positive and obligate anaerobic rod bacterium. CB can modulate the composition of the gut microbiome and promote the growth of beneficial microbes in the intestine by generating short-chain fatty acids (SCFAs), which in turn protect against colitis and prevents the formation of inflammatory-associated colorectal cancer (CRC) by ameliorating colon inflammatory processes. Yet, it remains unclear whether the culture and supernatant of CB could directly influence inflammatory CRC in mice. In this study, azoxymethane (AOM)+dextran sodium sulphate (DSS) was used to induce CRC model in C57BL/6 mice. Next, the serum levels of inflammatory cytokines, including interleukin-6 (IL-6), interleukin-10 (IL-10), and cytokines TNF-α, were measured and the pathohistological examination of the large intestine was performed. Both CB culture and supernatant were found to have anti-inflammatory properties. Subsequently, Western blot and Real-Time Quantitative PCR (RT-qPCR) revealed that CB and supernatant regulate the NF-κB/p65 pathway to inhibit the development and progression of inflammatory CRC in AOM+DSS-treated mice, which could be due to the high levels of butyric acid in the supernatant.